On the definition and interpretation of voice selective activation in the temporal cortex - Bethmann, Anja; Brechmann, André (Frontiers in Human Neuroscience, 2014)
Regions along the superior temporal sulci and in the anterior temporal lobes have been found to be involved in voice processing. It has even been argued that parts of the temporal cortices serve as voice-selective areas. Yet, evidence for voice-selective activation in the strict sense is still missing. The current fMRI study aimed at assessing the degree of voice-specific processing in different parts of the superior and middle temporal cortices. To this end, voices of famous persons were contrasted with widely different categories, which were sounds of animals and musical instruments. The argumentation was that only brain regions with statistically proven absence of activation by the control stimuli may be considered as candidates for voice-selective areas. Neural activity was found to be stronger in response to human voices in all analyzed parts of the temporal lobes except for the middle and posterior STG. More importantly, the activation differences between voices and the other environmental sounds increased continuously from the mid-posterior STG to the anterior MTG. Here, only voices but not the control stimuli excited an increase of the BOLD response above a resting baseline level. The findings are discussed with reference to the function of the anterior temporal lobes in person recognition and the general question on how to define selectivity of brain regions for a specific class of stimuli or tasks. In addition, our results corroborate recent assumptions about the hierarchical organization of auditory processing building on a processing stream from the primary auditory cortices to anterior portions of the temporal lobes.